Why Have Policies on Private Education Been Slow to Make Progress? Observations from the Perspective of Organizational Behavior and Decision Making. Issue 1 (4th March 2019) - Fengqiao, Yan
Abstract: Private education in our country is a novelty that has grown up outside the public education system, and the formulation and implementation of policies on private education often involves several government departments, in an act of cooperative decision making between multiple government departments. As a result, the effectiveness of the formulation and implementation of policies on private education is, in a certain sense, dependent on the degree of coordination between various government departments, while also being subject to the impact of whether timely adjustments have been made to existing regulations. This characteristic of policies on private education is suited to analysis from the perspective of organizational behavior and decision-making models. The slow progress on the three private education policies related to reasonable returns, independent colleges, and categorized management is a typical example of organizational behavior and decision-making models.